The Influence Of Learning Models On Students' Integrated Economic Sciences Learning Outcomes - Supriyadi, Supriyadi (International Journal of Business, Law, and Education, 2023)
This research aims to reveal the influence of the learning model on the economics integrated social science (IPS) learning outcomes of Setu Bekasi State Junior High School (SMP) 1 students. The research method used is quantitative research with an experimental approach. The population in this study was class VIII students at SMP Negeri 1 Setu Bekasi, totaling 400 students. The sample used in this research was divided into two classes, namely class VIII.1 which was the experimental class with 40 students and class VIII.2 which was the control class with 40 students. The experimental class applies power point learning media and the control class uses conventional learning media. Data collection for this research used an integrated Social Studies Economics learning outcomes test. The data analysis technique uses comparative quantitative. The hypothesis testing method used is t test analysis. The research results revealed: The t test calculation was 0.000 < 0.05, or Ho was rejected. Thus the hypothesis proposed is supported by empirical data and from the results of further tests it can be seen that the learning outcomes of students who use Power Point media are higher than students who use conventional media, so it can be concluded that Power Point learning media influences the learning outcomes of class VIII students in integrated economics social studies subject at SMPN 1 Setu Bekasi